Character Portraits Of The Fifth And Sixth Emirs Of Bukhara - Makhammadiev Abror Toshkentovich (Genius Publishing Group, 2025)
This article analyzes the personalities and activities of two emirs who ruled in the Bukhara Emirate but remained relatively unknown in history. The study sheds light on the reigns of Amir Haydar’s two sons: the fifth emir, Husayn, who ruled for over two months, and the sixth emir, Umar, who ruled for four months. The analysis is based on contemporary sources and later research studies.
Keywords: Manghits; Bukhara; Amir Haydar; defense